The Global Prevalence of Amblyopia in Children: A Systematic Review and Meta-Analysis - Budan Hu; Zongshun Liu; Jiao Zhao; Li Zeng; Gengsheng Hao; Dan Shui; Ke Mao (Frontiers Media S.A., 2022)
Epidemiological data about the prevalence of amblyopia around the world vary widely among regions and periods. This meta-analysis aimed to determine the global prevalence of amblyopia in children. PubMed, Embase, and the Cochrane Library were searched for prevalence studies published up to 5 November 2021. The outcome was the prevalence of amblyopia, analyzed as pooled estimates with 95% confidence intervals (CI). A total of 97 studies were included, including 4,645,274 children and 7,706 patients with amblyopia. The overall worldwide pooled prevalence of amblyopia was 1.36% (95%CI: 1.27-1.46%). The prevalence of amblyopia was higher in males (1.40%, 95%CI: 1.10-1.70%) than in females (1.24%, 95%CI: 0.94-1.54%) (OR = 0.885, 95%CI: 0.795-0.985, P = 0.025). The results of the meta-regression analysis showed that there were no significant associations between the prevalence of amblyopia and geographical area, publication year, age, sample size, and whether it was carried out in a developed or developing country (all P > 0.05). Begg's test (P = 0.065) and Egger's test (P < 0.001) showed that there was a significant publication bias in the prevalence of amblyopia. In conclusion, amblyopia is a significant vision problem worldwide, and public health strategies of early screening, treatment, and management are important.